Pemanfaatan Sistem Informasi Perpustakaan Digital Berbasis Website Untuk Para Penulis - Agus Prayitno; Yulia Safitri - AMIK BSI Jakarta (Universitas Bina Sarana Informatika, 2015)
Abstract - Libraries in general is a place that provides a collection of books and records in physical form. Libraries in general are managed by government agencies. As technology advances, a library can be converted into a digital library that can be accessed anywhere and anytime. The existence of digital libraries can provide solutions to problems that exist among them, the lack of information providers container. Digital library that has been built not only functions as a provider of information, but a container that is able to accommodate the work of local authors. The digital library is built using Adobe Dreamweaver CS6, accompanied by CSS (Cascading Style Sheet) and MySQL so that the process of website development can be faster and easier. The purpose of making this digital library website that is providing a public service that is accessible to all levels of society. While the library's collection is all of the work donated by donors in the form of a digital library. Before the results of the work was published, the administrator will be to check the contents of the collection that had been donated. This is done as a filter if the collection is worth to be published or not. Keywords:Information Systems, Web-Based Digital Library